Actual Problems of Corpus Delicti of the Crime on the Creation, Organization and Management of Pyramid Schemes - Hovhannisyan, Arman; Petrosyan, Levon (Bulletin of Yerevan University C: Jurisprudence, 2021)
Within the framework of this article, the crime of creating, organizing or managing a financial pyramid has been studied in detail. Analyzing the crime in the light of foreign regulations, practical cases and the draft Criminal Code of the Republic of Armenia, a number of shortcomings related to the article were revealed, the solution of which can result in making the article applicable in reality, giving adequate qualifications to many publicly dangerous situations.
Keywords: financial pyramid; fraud; lawful multi-layered marketing; illegal and fake business; scheme